Function and Meaning of Palembang Songket Fapric Decorative Varieties - Andini, Septia Sulia; Susanti, LR Retno (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
Songket is a typical Malay cloth, many areas in Sumatra have Songket cloth. However, of these many areas, Palembang Songket Cloth is the most famous. Palembang's typical songket is famous for its beauty and luxury. Songket itself is a form of high culture from the Sriwijaya era that is full of meaning. Therefore, this research wants to examine more deeply the meaning of various motifs and functions of various types of Songket. This research uses the historical method with stages of heuristics, criticism, interpretation and historiography. It is hoped that the results of this research will provide satisfactory results. The research results show that each motif depicted on a piece of Songket cloth has its own meaning, this meaning generally describes the greatness of Srivijaya as a great kingdom.